Osteosarcoma Phenotype Is Inhibited by 3, 4-Methylenedioxy-β-nitrostyrene. (31st May 2012) - Messerschmitt, Patrick J.; Rettew, Ashley N.; Schroeder, Nicholas O.; Brookover, Robert E.; Jakatdar, Avanti P.; Getty, Patrick J.; Greenfield, Edward M.
Abstract : β-nitrostyrene compounds, such as 3, 4-methylenedioxy-β-nitrostyrene (MNS), inhibit growth and induce apoptosis in tumor cells, but no reports have investigated their role in osteosarcoma. In this study, human osteosarcoma cell families with cell lines of varying tumorigenic and metastatic potential were utilized. Scrape motility assays, colony formation assays, and colony survival assays were performed with osteosarcoma cell lines, both in the presence and absence of MNS. Effects of MNS on human osteoblasts and airway epithelial cells were assessed in monolayer cultures. MNS decreased metastatic cell line motility by 72–76% and colony formation by 95–100%. MNS consistently disrupted preformed colonies in a time-dependent and dose-dependent manner. MNS had similar effects on human osteoblasts but little effect on airway epithelial cells. An inactive analog of MNS had no detectable effects, demonstrating specificity. MNS decreases motility and colony formation of osteosarcoma cells and disrupts preformed cell colonies, while producing little effect on pulmonary epithelial cells.